2015
DOI: 10.1038/gt.2015.105
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastomas vary widely in their sensitivities to herpes simplex virotherapy unrelated to virus receptors and susceptibility

Abstract: Although most high-risk neuroblastomas are responsive to chemotherapy, relapse is common and long-term survival is less than 40%, underscoring the need for more effective treatments. We evaluated the responsiveness of 12 neuroblastoma cell lines to the Δγ134.5 attenuated oncolytic HSV, Seprehvir (HSV1716), which is currently used in pediatric phase I trials. We found that entry of Seprehvir in neuroblastoma cells is independent of the expression of nectin-1 and the sum of all four known major HSV entry recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…The in vitro HSV entry molecule expression and cytotoxicity data suggest that SARC-45 may be more susceptible than SARC-28 to infection with M002; however, the virus replicated equally in both cell lines after 24 hr of infection, and entry receptor molecule expression does not always correlate with higher viral entry. 23 Our in vivo studies examining the response to a single dose of M002 in immunocompromised mice bearing SARC-28 and SARC-45 in an immunoprivileged location confirmed the significant oncolytic effect of M002 in the absence of an adaptive host immune system. Previous studies demonstrated that human alveolar and embryonal rhabdomyosarcoma and renal sarcoma cell lines with high expression of CD111 were sensitive to in vitro killing by oHSV.…”
Section: Discussionsupporting
confidence: 65%
“…The in vitro HSV entry molecule expression and cytotoxicity data suggest that SARC-45 may be more susceptible than SARC-28 to infection with M002; however, the virus replicated equally in both cell lines after 24 hr of infection, and entry receptor molecule expression does not always correlate with higher viral entry. 23 Our in vivo studies examining the response to a single dose of M002 in immunocompromised mice bearing SARC-28 and SARC-45 in an immunoprivileged location confirmed the significant oncolytic effect of M002 in the absence of an adaptive host immune system. Previous studies demonstrated that human alveolar and embryonal rhabdomyosarcoma and renal sarcoma cell lines with high expression of CD111 were sensitive to in vitro killing by oHSV.…”
Section: Discussionsupporting
confidence: 65%
“…However, T‐01 had no detectable effect on HLE and JHH‐5 cells, likely because of the relatively low levels of T‐01 replication (Figure ). It cannot negate the possibility that the entry efficiency of T‐01 into cells and/or the expression levels of HSV receptors on cell lines used were involved in the cytopathic activities of T‐01 in addition to the levels of T‐01 replication . Such information may help to elucidate why some tumors are highly sensitive to oHSV, and may lead to methods for selecting patients with the most sensitive tumors in oHSV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is abundant evidence that HSV-1 mutants deficient in the ␥ 1 34.5 gene have oncolytic activities. This has been shown for tumors, including in the brain, colon, ovarian, breast, liver, and skin, in immunodeficient as well as in immunocompetent preclinical models (24)(25)(26)(27)(28)(29)(30)(31). However, the antitumor outcomes vary widely.…”
mentioning
confidence: 98%
“…For example, HSV1716 is highly potent against hepatocellular carcinoma (30). With respect to neuroblastomas, HSV1716 exhibits activities from a complete response in the CHP-134 model to a mild effect in the SK-N-AS model (31). The underlying events are complex, but the nature of virus-host interactions seems a determinant.…”
mentioning
confidence: 99%